Improving Access to Refractive Services in Adults: A Health Examination Center-Based Model - Lin, Haishuang; Sun, Jing; Congdon, Nathan; Xu, Meiping; Liu, Shanshan; Liang, Yuanbo; Wang, Hailin; Zhang, Shaodan (Frontiers in Medicine, 2021)
Purpose: To assess the potential of a health examination center-based screening model in improving service for uncorrected refractive error. Methods: Individuals aged ≥18 years undergoing the routine physical examinations at a tertiary hospital in the northeast China were invited. Presenting visual acuity, noncycloplegic autorefraction, noncontact tonometry, fundus photography, and slit-lamp examination were performed. Refractive error was defined as having spherical equivalent ≤ -0.75 D or ≥ +1 D and uncorrected refractive error was considered as refractive error combined with presenting visual acuity < 6/12 in the better eye. Costs for the screening were assessed. Results: A total of 5,284 participants (61 ± 14 years) were included. The overall prevalence of myopia and hyperopia was 38.7% (95% CI, 37.4–40.0%) and 23.5% (95% CI, 22.3–24.6%), respectively. The prevalence of uncorrected refractive error was 7.85% (95% CI, 7.13–8.58%). Women (p < 0.001 and p = 0.003), those with age ≥ 70 years (p < 0.001 and p = 0.003), and myopia (p < 0.001 and p < 0.001) were at higher risk of uncorrected refractive error and uncorrected refractive error-related visual impairment. Spectacle coverage rate was 70.6% (95% CI, 68.2–73.0%). The cost to identify a single case of refractive error and uncorrected refractive error was US$3.2 and US$25.2, respectively. Conclusion: The prevalence of uncorrected refractive error is high in the urban Chinese adults. Health examination center-based refractive error screening is able to provide an efficient and low-cost model to improve the refractive services in China.